A corpus-based approach to contemporary Irish writing: Ross O’Carroll-Kelly’s use of «like» as a discourse marker - Amador Moreno, Carolina P. (International Journal of English Studies, 2012)
This paper analyses in quantitative and qualitative terms the representation of the discourse marker like in contemporary Irish English writing. A common feature of contemporary spoken English, the discourse marker like seems to have made its way into the English spoken in Ireland, as portrayed by contemporary Irish authors such as Paul Howard. Howard, whose narrative can be taken as an example of oral writing, has been acclaimed by critics as having an exceptionally fine ear for Dublin English, but what is this acclamation based on? The paper argues that the findings of corpus stylistics (comparative frequencies, distributions, etc.) document in a more systematic way what literary critics and readers may intuitively deduce. By analysing the syntactic and pragmatic behaviour of like in Howard’s fictional discourse, this paper aims to show the value of the combination of computer methodology and literary interpretation in evaluating the representation of fictional dialect.